Ta thực hiện theo các bước sau :
Bước 1 : Biến đổi
\(a_1\sin^2x+b_1\sin x\cos x+c_1\cos^2x=\left(A\sin x+B\cos x\right)\left(a_2\sin x+b_2\cos x\right)+C\left(\sin^2x+\cos^2x\right)\)
Bước 2 : Khi đó :
\(I=\int\frac{\left(A\sin x+B\cos x\right)\left(a_2\sin x+b_2\cos x\right)+C\left(\sin^2x+\cos^2x\right)}{a_2\sin x+b_2\cos x}\)
\(=\int\left(A\sin x+B\cos x\right)+C\int\frac{dx}{a_2\sin x+b_2\cos x}\)
= \(-A\cos x+B\sin x+\sqrt{\frac{C}{a^2_a+b_2^2}}\int\frac{dx}{\sin\left(x+\alpha\right)}\)
=\(-A\cos x+B\sin x+\frac{C}{\sqrt{a_2^2+b^2_2}}\ln\left|\tan\frac{x+\alpha}{2}\right|+C\)
Trong đó :
\(\sin\alpha=\frac{b_2}{\sqrt{a_2^2}+b^{2_{ }}_2};\cos\alpha=\frac{a_2}{\sqrt{a_2^2}+b^{2_{ }}_2}\)
Đúng 0
Bình luận (0)